A STUDY ON INSURANCE SAMADHAN: TO MEET THE UNMET NEEDS OF MISTREATED POLICYHOLDERS (International Journal of Food and Nutritional Sciences, 2022)
Numerous customers claim that their insurance providers misled them. Therefore, to address this issue, Insurance Samadhan, a grievance redressal organization, sends specialists from the insurance industry to assist an individual so they can discuss their case and aid in finding a suitable resolution for their grievances. Insurance Samadhan can deal with any issue relating to insurance, such as lapsed insurance policies, assistance with case resolution, claim recovery in the event of insurance fraud, support for NRIs in keeping their policies, and much more. To understand the experiences of policyholders and their awareness regarding the services of Insurance Samadhan, 122 policyholders were surveyed.The findings indicate that Insurance Samadhan and the services it provided were unfamiliar to the respondents. People also believe that applying for and claiming insurance involves too many hurdles. They also believe that there are too many vague terms used in the documentation process. Many customers had trouble getting their insurance claim because it was totally or partially rejected.